1997
DOI: 10.1007/s000110050175
|View full text |Cite
|
Sign up to set email alerts
|

Anti-arthritic activity of hydroxamic acid-based pseudopeptide inhibitors of matrix metalloproteinases and TNFα processing

Abstract: Thus, these novel compounds offer a new disease modifying therapy for arthritis and the results also suggest that inhibition of TNF alpha production may contribute, at least in part, to their anti-arthritic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 13 publications
1
42
0
Order By: Relevance
“…In this study, we have demonstrated the induction of MMP-9 in primary human mast cells by a proinflammatory cytokine (TNF-␣), a cytokine strongly linked to the pathogenesis of RA (45). The TNF-mediated up-regulation of MMP-9 was strongly abrogated by IFN-␥.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In this study, we have demonstrated the induction of MMP-9 in primary human mast cells by a proinflammatory cytokine (TNF-␣), a cytokine strongly linked to the pathogenesis of RA (45). The TNF-mediated up-regulation of MMP-9 was strongly abrogated by IFN-␥.…”
Section: Discussionmentioning
confidence: 87%
“…TNF-␣ plays a key role in the pathogenesis of RA and is currently a therapeutic target in this and other inflammatory diseases (45). TNF-␣ positively regulates expression of MMPs that FIGURE 3.…”
Section: Cytokine Regulation Of Mast Cell-derived Mmp-9mentioning
confidence: 99%
“…Stimulation of TNF-␣ release from monocytes in human blood has been studied both in vivo and in vitro after LPS challenge (Mohler et al, 1994;DiMartino et al, 1997). The production of human TNF-␣ has been documented in vivo both clinically in sepsis patients and experimentally, after healthy volunteers received systemic LPS (Tracey et al, 1993;Dekkers et al, 1999).…”
Section: Ro 32-7315 An Orally Active Inhibitor Of Tumor Necrosis Facmentioning
confidence: 99%
“…The production of human TNF-␣ has been documented in vivo both clinically in sepsis patients and experimentally, after healthy volunteers received systemic LPS (Tracey et al, 1993;Dekkers et al, 1999). The majority of reported in vitro studies used primary cells in culture or tumor lines (Gearing et al, 1994;DiMartino et al, 1997). Although these systems have provided valuable information, they cannot take account of the complexities that can occur in whole blood such as protein binding, compartmentalization, and possible interactions between different cell types.…”
Section: Ro 32-7315 An Orally Active Inhibitor Of Tumor Necrosis Facmentioning
confidence: 99%
See 1 more Smart Citation